Pengaruh Product Quality, Location Dan Price Terhadap Keputusan Pembelian (Studi Kasus Pada Customer Resident Jaya Farm) - Zidane, Muhamad Yazid; Widarko, Agus; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract  This study is to determine the effect of product quality, location and price on purchasing decisions, a case study on customer Resident Jaya Farm. The population in this study are customers who have made transactions or purchases at the Resident Jaya Farm. The sampling method is non-probability sampling with an accidental sampling technique. Data collection method by providing questionnaires filled out by 75 respondents. The results showed that simultaneously product quality, location and price had a significant effect on purchasing decisions in case studies on customer Resident Jaya Farm. Variable of product quality does not effect on purchasing decisions, variable of location shows a significant effect on purchasing decisions and variable of price shows a significant effect on purchasing decisions in case studies on customer Resident Jaya Farm. Keywords : Product Quality, Location, Price, Purchasing Decisions, and Resident Jaya Farm Customer.